2020
DOI: 10.1038/s41565-020-0656-y
|View full text |Cite
|
Sign up to set email alerts
|

Banning carbon nanotubes would be scientifically unjustified and damaging to innovation

Abstract: Banning carbon nanotubes would be scientifically unjustified and damaging to innovation. Nature Nanotechnology, (2020). 15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…However, it is noted that we have only studied one type of MWCNTs, and one cannot extrapolate the findings to other types of single or multi-walled CNTs. Indeed, grouping all CNTs into one material category is scientifically unjustified and may hinder innovation [ 57 , 58 ]. Therefore, further studies are needed to fully address the physicochemical properties that are responsible for the observed biological or toxicological effects of CNTs [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noted that we have only studied one type of MWCNTs, and one cannot extrapolate the findings to other types of single or multi-walled CNTs. Indeed, grouping all CNTs into one material category is scientifically unjustified and may hinder innovation [ 57 , 58 ]. Therefore, further studies are needed to fully address the physicochemical properties that are responsible for the observed biological or toxicological effects of CNTs [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…as possibly carcinogenic for humans ( 5 ). The numerous applications of other CNT justify the need of carefully characterizing the mesotheliomagenic potential ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely the result of the concerns raised over their morphological similarity to asbestos fibers, even though it is demonstrated that chemical functionalization [ 79 ] and fine control over the hydrogel stiffness [ 80 ] can alleviate their pathogenicity. Furthermore, given the large diversity of available CNT types [ 70 ], and the fact that their biocompatibility depends on a plethora of factors [ 81 ], it becomes apparent that alarming generalizations that pose innovation barriers should be avoided [ 82 ].…”
Section: Recent Advancements On Hydrogels With Carbon Nanomaterials For Medicinementioning
confidence: 99%